Redesigning a food bank supply chain network, Part I: Background and mathematical formulation - C. L. Martins; Teresa Melo; Margarida Vaz Pato (Hochschule für Technik und Wirtschaft des Saarlandes, Fakultät für Wirtschaftswissenschaften, 2016)
Motivated by the increasing global interest in reducing food waste, we address the problem of redesigning a multi-echelon supply chain network for the collection of donated food products and their distribution to non-profit organisations that provide food assistance to the needy population. For the social enterprise managing the network, important strategic decisions comprise opening new food bank warehouses and selecting their storage and transport capacities from a set of discrete sizes over a multi-period planning horizon. Facility decisions also affect existing food banks that may be closed or have its capacity expanded. Logistics decisions involve the number of organisations to be supplied, their allocation to operating food banks and the flow of multiple food products throughout the network. Decisions must be made taking into account that food donations are insufficient and a limited investment budget is available. The paper is organised in two parts. In Part I, we propose a novel mixed-integer linear programming model that captures various practical features of a food aid supply chain. In particular, sustainability is explicitly accounted for within the decision-making process by integrating economic, environmental and social objectives. In Part II, a computational study is conducted to investigate the trade-offs achieved by considering three conflicting objective functions. Numerical results are presented for real-case based instances shaped by the food bank network coordinated by the Portuguese Federation of Food Banks.
Keywords: 650; supply chain; sustainability; tri-objective problem; MILP model